Recent Development of Techniques and Devices in Colorectal Endoscopic Submucosal Dissection - Hiroya Mizutani; Satoshi Ono; Daisuke Ohki; Chihiro Takeuchi; Seiichi Yakabi; Yosuke Kataoka; Itaru Saito; Yoshiki Sakaguchi; Chihiro Minatsuki; Yosuke Tsuji; Keiko Niimi; Shinya Kodashima; et al. (Korean Society of Gastrointestinal Endoscopy, 2017)
Colorectal endoscopic submucosal dissection (ESD) is now a well-established endoscopic treatment for early-stage colorectal neoplasms, especially in Asian countries, including Japan. Despite the spread of colorectal ESD, there are still situations in which achieving successful submucosal dissection is difficult. Various novel techniques and devices have been developed to overcome these difficulties, and past reports have shown that some of these strategies can be applied to colorectal ESD. We review several recent developments in the field. The techniques reviewed include the pocket creation method and traction methods and the devices reviewed include the overtube with balloon and electrosurgical knives with water-jet function. These improved techniques and devices can facilitate safer, more reliable ESDs and expand its applicability and acceptability all over the world.